Multiple Approaches to Robust Speech Recognition - Liu, Fu-Hua; Acero, Alex; Stern, Richard M. (Proc. of the ICSLP, 1992)
As automatic speech recognition systems are finding their way into practical applications it is becoming increasingly clear that they must be able to accommodate a variety of acoustical environments. This paper describes two algorithms that provide robustness for automatic speech recognition systems in a fashion that is suitable for real-time environmental normalization for workstations of moderate size.